The Influence of Oral and Written Corrective Feedback on Writing Apprehension among Introvert and Extrovert EFL Students - Natalia Manuhutu; Ruckmana Fachrul Islam; Sri Winarsih; Dewi Sartika; Lanlan Muhria (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the influence of oral and written feedback on writing apprehension among introvert and extrovert EFL students using a 2 x 2 factorial design. A total of 108 university students, 47 introverts and 61 extroverts identified using the Eysenck Personality Inventory, participated in the study. Writing apprehension was measured using a validated questionnaire after students received both oral and written feedback during writing instruction. Paired samples t-tests revealed that introvert students experienced significantly higher writing apprehension when receiving oral feedback (t = 6.82, p < .001), while extrovert students reported significantly higher apprehension with written feedback (t = 4.23, p < .001). Two-way ANOVA results revealed significant main effects of personality type (F = 10.321, p = .002) and feedback mode (F = 5.921, p = .027). Importantly, a significant interaction effect was also found between personality type and feedback mode (F = 10.567, p = .002), indicating that students’ responses to feedback varied depending on their personality. Specifically, introvert students reported greater writing apprehension with oral feedback, whereas extrovert students experienced more apprehension with written feedback. These findings underscore the importance of adapting feedback strategies to individual learner characteristics. Tailoring feedback to align with students’ personality traits can help reduce writing apprehension and enhance instructional effectiveness in EFL writing classrooms.